?SCREENING OF FRESH ANIMAL MILK FOR LEAD CONTAMINATION - Ashraf, Waqar; ]affar, M; Masud, Khalid (Biological Sciences - PJSIR, 2000)
Fresh milk samples of buffalo, goat and cow from different urban and rural locations falling within and outside the proximity of the highways of Punjab and NWFP were analysed for lead using the atomic absorption method. The possibility of anthropogenic contamination of lead in the milk samples was explored. Lead concentration of varying levels wasfound in themilkofanimals habitatingnear highwaylocations inboththeprovinces.In general, maximum leadlevelwasfoundinthegoatmilk,whiletheminimuminbuffalomilk.Theaverageconcentration wereO.082,0.098 and0.173mg 1.1fornearhighwayand0.062,0.044and0.142 mgl' foroff-highwayanimalsinthemilksofbuffalo,cow and goat, respectively.The provincewise comparison showedmorecontamination of lead inthe milkof animals from NWFP.Compared with international standards, the localmilk was found unsafe in terms of lead content.